2020
DOI: 10.3390/coatings10030201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Streptococcus Mutans Adhesion to the Surface of Biomimetically-Modified Orthodontic Archwires

Abstract: Bacterial adhesion and biofilm formation on the surfaces of dental and orthodontic biomaterials is primary responsible for oral diseases and biomaterial deterioration. A number of alternatives to reduce bacterial adhesion to biomaterials, including surface modification using a variety of techniques, has been proposed. Even though surface modification has demonstrated a reduction in bacterial adhesion, information on surface modification and biomimetics to reduce bacterial adhesion to a surface is scarce. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Likely, the enhanced hydrophobicity of the surface of the substrates, as seen by the increase in the surface contact angle, impairs S. mutans attachment and growth [30]. It has been shown that the bacterial surface of S. mutans is highly hydrophilic and displays a preference for higher bacterial adhesion to hydrophilic surfaces [31]. Further studies are required over a longer period to see the long-term impacts of S. mutans inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, the enhanced hydrophobicity of the surface of the substrates, as seen by the increase in the surface contact angle, impairs S. mutans attachment and growth [30]. It has been shown that the bacterial surface of S. mutans is highly hydrophilic and displays a preference for higher bacterial adhesion to hydrophilic surfaces [31]. Further studies are required over a longer period to see the long-term impacts of S. mutans inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these topographical changes are inspired by nature, mimicking the architecture of animal skin (i.e., shark, cicada, and dragonfly wings) and vegetal surfaces (i.e., lotus, rose petals) [ 141 ]. For example, Arango-Santander et al (2020) modified the surface of orthodontic archwires, mimicking the surface of Colocasia esculenta leaves resulting in reduced adhesion and colonization of S. mutans compared to unmodified wires [ 142 ] . Another example are the mussel-inspired catechols (i.e., polydopamine (PDA) and dopamine) for surface functionalization and bonding in wet enviroments [ 143 ].…”
Section: Smart Dental Materials For Antimicrobial and Antibiofilm The...mentioning
confidence: 99%
“…The topographies from these leaves were duplicated using PDMS and stainless steel and titanium alloys surfaces, used for orthodontic purposes, were modified. The results showed an important reduction in bacterial adhesion to such surfaces, except the stainless-steel surface that was modified using the S. molesta topography, which showed an increase in adhesion [ 38 , 39 ].…”
Section: Bioinspiration From Vegetal Surfacesmentioning
confidence: 99%
“…An additional advantage of physical surface modification is that the well-known techniques used to modify the topography of biomaterials may reduce research expenses [ 27 ]. Topographic modification of artificial materials using natural surfaces as inspiration has been used in fields as diverse as marine applications to avoid fouling or reduce drag [ 24 , 28 , 29 , 30 , 31 ], preservation and safety of food products [ 32 , 33 ] or biomedical sciences [ 34 , 35 , 36 , 37 , 38 , 39 ], among many others.…”
Section: Introductionmentioning
confidence: 99%